Aguardenteiros do Piranga: família, produção da riqueza e dinâmica do espaço em zona de fronteira agrícola. Minas Gerais, 1800-1856 - Gusthavo Lemos (2012)
This thesis discusses the impact of the intergenerational transmission of property on the rural dynamics and land structure, that is, on the organization of the rural world. It focuses on the parish of Guarapiranga between the late eighteenth century and the first half of the nineteenth century. The core of the analysis rests on the social group engaged with the sugarcane breeding and transformation, especially the producers of cachaça. We identified the family institution as the foundation upon which rested the mode of the rural world organization and as the axis around which revolved all spheres of life. Therefore, in a pre-industrial world, devoid of many of the modern social institutions, family concentrated a power of decision on the organization and reproduction of society and economy. We designate as lógica familística all this power of influence of family. Thus, the transmission processes acquire great prominence, since the continuity or otherwise of production units depended, in a way, on the success of the intergenerational exchanges of wealth. Finally, we realize that the group of the cachaça producers settled as the local agrarian elite, which, by strategic uses of the assets transferring mechanisms and their privileged economic position, dominated the best farmlands in the region, especially the Valley of the Piranga River. As a result, the land distribution was extremely unequal in the parish.